The endothelium: an active regulator of lipid and glucose homeostasis - Safatul Hasan, Sana; Fischer, Andreas (Trends in cell biology, 2021)
The vascular endothelium serves as a dynamic barrier that separates blood from interstitia. Endothelial cells (ECs) respond rapidly to changes in the circulation and actively regulate vessel tone, permeability, and platelet functions. ECs also secrete angiocrine factors that dictate the function of adjacent parenchymal cells in an organ-specific manner. Endothelial dysfunction is considered as a hallmark of metabolic diseases. However, there is emerging evidence that ECs modulate the transfer of nutrients and hormones to parenchymal cells in response to alterations in metabolic profile. As such, a causal role for ECs in systemic metabolic dysregulation can be envisaged. This review summarizes recent progress in the understanding of regulated fatty acid, glucose, and insulin transport across the endothelium and discusses its pathophysiological implications.